The influence and optimisation of electrical parameters for enhanced coalescence under pulsed DC electric field in a cylindrical electrostatic coalescer. (22nd December 2015) - Yang, Donghai; Xu, Minghai; He, Limin; Luo, Xiaoming; Lü, Yuling; Yan, Haipeng; Tian, Chengkun
Abstract: A pulsed DC electric field is usually used to enhance drop–drop and drop–interface coalescence in a water-in-oil (W/O) emulsion. The effect and optimisation of electrical parameters are important when designing an electrostatic coalescer. In this work, experiments were performed with a small-scale electrostatic coalescer and image processing technology using water in crude oil emulsions to investigate the influence of electric field intensity, frequency, duty ratio and rise time. The comparison between experimental data and predicted data based on the two-layer capacitor model of a cylindrical electro-coalescer was also obtained to validate whether the two-layer capacitor model is applicable for a concentric cylindrical electrostatic coalescer. Optimum electric field strength exists for different water content emulsions (525.6 kV m −1 for water content of 10% and 338.1 kV m −1 for 30%), which suggests that it is higher for lower water content emulsion. There are two optimum frequencies in the low and high frequency ranges. For water content of 10%, the optimum frequency is approximately 20 Hz, while for 30%, it is 10 Hz in the low frequency range. The coalescence effect is also high when the frequency is 2000 Hz. The droplet diameter is largest when the duty ratio is 50% for different electric field strengths, frequencies and water contents. The effect of rise time for pulsed DC is negative and the longer the rise time is, the worse the electrostatic coalescence effect is. The optimum frequency and duty ratio are obtained by using a theoretical formula and an empirical formula. The optimum frequency is nearly the same for the low frequency range especially for emulsions with a water content of 10%, but coalescence effects will increase at high frequency, which is different from the theoretical predicted value, indicating that the theory is applicable in the low frequency range for the concentric cylindrical coalescer. The predicted duty ratio is close to 0.5 and is nearly the same as the experimental results. In the electrostatic coalescer, the waveform of pulsed DC will be distorted to a triangle wave at high frequency. The high-frequency pulsed DC electric field is therefore not suitable for use in an electrostatic coalescer with an insulated electrode. Graphical abstract: Highlights: The influence and optimisation of electrical parameters under pulsed DC electric field were investigated through experiments. Optimum electric field frequency and duty ratio were calculated based on two-layer capacitor theory. The two-layer capacitor theory is applicable in the low frequency range for a concentric cylindrical coalescer. The pulsed DC waveform is easily distorted when frequency is high.